The fishes from the Coto River basin, Pacific coast, Costa Rica - Angulo, Arturo; Gil-León, Jorge San; Oviedo-Soto, Alejandro; Abarca-Odio, Juan I.; Umaña-Villalobos, Gerardo (Zootaxa, 2020)
A checklist of the fishes of the Coto River basin, southern Pacific, Costa Rica, compiled from field and museum surveys is presented. A total of 61 species, representing 48 genera, 26 families and 11 orders are listed. Peripheral species were dominant (44.3%), whereas secondary and primary freshwater species represented 32.8% and 23.9% of the total diversity. The orders Cyprinodontiformes (12 spp.) and Perciformes (11) and the families Poeciliidae (8) and Cichlidae (7) were the most diverse. Two species (Lutjanus guttatus and Polydactylus approximans) were new records for Costa Rican freshwaters and ten additional species were found to have expanded geographical ranges. An identification key and a complete photographic album of all fish species recorded are presented. This investigation provides a framework for future studies on fishes from this area complementing previous efforts seeking to increase our knowledge about the freshwater ichthyofauna of the central and southern Pacific regions of Costa Rica.